Preparation method of catalyst for photocatalytic degradation of waste plastics and hydrogen production

By doping NiCo-LDH in ZnCdS2 photocatalyst to form ZnCdS2-NiCo photocatalyst, the existing ZnCdS2 photocatalyst has solved the problem of high photogenerating electrons and hole recombination efficiency and few surfactant sites and significantly improved the photocatalytic activity. It achieves the effect of efficient degradation of waste plastics and hydrogen production.

CN119488923APending Publication Date: 2025-02-21GUANGXI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411594458.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing ZnCdS2 photocatalyst has high photogenerated electrons and hole recombination efficiency, resulting in low photocatalytic activity and few surfactant sites, limiting the rate of redox reaction.

Method used

By doping NiCo-LDH into ZnCdS2, a ZnCdS2-NiCo photocatalyst is formed, and the catalyst is prepared by hydrothermal reaction and drying steps to improve its photocatalytic activity.

Benefits of technology

It significantly improves the separation efficiency and surface activity of photogenerated charges, improves photocatalytic activity, and can efficiently degrade waste plastics and produce hydrogen under visible light, with a hydrogen production rate of 48.62mmol·g-1·h-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488923A_ABST
    Figure CN119488923A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a catalyst for photocatalytic degradation of waste plastics and hydrogen production, which comprises the following steps: (1) dissolving Ni (Ac) 2.4 H2O in methanol, adding ZIF-67 powder, and stirring; and carrying out hydrothermal treatment, filtering, washing and drying to obtain NiCo-LDH powder. (2) dissolving thioacetamide in ethanol; mixing the NiCo-LDH powder with an aqueous solution of Cd (Ac) 2.2 H2O and Zn (Ac) 2.2 H2O, and then adding the NiCo-LDH powder and stirring; and finally, carrying out hydrothermal treatment, filtering, washing and drying to obtain the ZnCdS2-NiCo photocatalyst. According to the ZnCdS2-NiCo photocatalyst disclosed by the invention, the charge separation efficiency and the surface activity are remarkably improved, the ZnCdS2-NiCo photocatalyst has high-activity photocatalytic performance, and the hydrogen evolution rate of the ZnCdS2-NiCo photocatalyst reaches 48.62 mmol.g <-1 >. H <-1 >; the preparation method is simple to operate, low in cost and easy for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental purification and energy recovery, and in particular to a method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen. Background Art

[0002] Plastic products are widely used in daily life, especially in industries such as catering, food, daily necessities and tools. About 80% of plastic waste is either discarded in the environment or landfilled, and these plastic wastes are complex, toxic and difficult to degrade. If not properly treated, these wastes can cause serious harm to humans, animals and plants. Therefore, recycling waste plastics has become an urgent problem that needs to be solved. To meet this challenge, photocatalytic reforming technology provides a solution that can convert waste plastics into valuable chemicals under mild conditions and produce hydrogen. This method not only helps to reduce plastic pollution, but also provides a renewable energy source, showing broad application prospects. However, the development of highly active photocatalysts for degrading waste plastics and producing hydrogen is the key to realizing this technology, which brings both opportunities and challenges.

[0003] ZnCdS2 photocatalyst has attracted extensive attention due to its energy band structure, which is very suitable for catalyzing the degradation of waste plastics (such as polylactic acid, polystyrene, polypropylene, etc.) and its simple preparation method. Under light conditions, ZnCdS2 photocatalyst is excited to generate photogenerated electron-hole pairs, in which the photogenerated holes will undergo oxidation reaction with the waste plastics adsorbed on the surface of ZnCdS2 photocatalyst, and the photogenerated electrons will undergo reduction reaction with water to produce hydrogen. However, the recombination efficiency of photogenerated electrons and holes is high, which limits the number of photogenerated electrons and holes that can participate in the redox reaction, resulting in low photocatalytic activity. In addition, the small number of active sites on the photocatalyst surface and the limited rate of redox reaction will also lead to low photocatalytic activity. Therefore, reducing the recombination of photogenerated electrons and holes and improving the surface catalytic activity, and improving the photocatalytic activity of ZnCdS2 have become the primary content of research.

[0004] Doping engineering has attracted widespread attention because it plays a vital role in regulating high surface activity and effective charge separation. Doping heteroatoms and ligand ions of different radii in photocatalysts will inevitably lead to lattice microstrain. The lattice strain of photocatalysts is conducive to the formation of vacancies (ZHANG S, ZHANG Z, SI Y, et al. Gradient Hydrogen Migration Modulated with Self-Adapting S Vacancy in Copper-Doped ZnIn2S4 Nanosheet for Photocatalytic Hydrogen Evolution[J]. ACS Nano, 2021, 15(9): 15238-48.). The combination of heteroatom doping and vacancies achieves the synergistic effect of doping engineering and defect engineering, optimizes surface reactions, significantly improves charge separation efficiency, and thus enhances photocatalytic activity (ZHU Y, DENG W, TAN Y, et al. In Situ Topochemical Transformation of ZnIn2S4 for Efficient Photocatalytic Oxidation of 5-Hydroxymethylfurfural to 2,5-Diformylfuran [J]. Adv Funct Mater, 2023, 33 (45): 2304985.). Compared with other non-magnetic elements, magnetic elements (such as Fe, Ni, Co, etc.) doped into photocatalysts can manipulate spin-polarized electrons. Under the spin polarization effect, the directions of photogenerated holes and photogenerated electrons do not match, and the recombination of photogenerated charges is reduced, thereby improving the charge separation efficiency. Therefore, by doping with magnetic elements, vacancies are induced to promote the reaction of hydroxide ions with photogenerated holes to generate hydroxyl radicals, which can more efficiently degrade waste plastics, and induce spin polarization to reduce the recombination of photogenerated electrons and holes, thereby improving photocatalytic activity. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen. The photocatalyst prepared by the method can effectively improve the separation efficiency and surface activity of photogenerated charges and enhance its photocatalytic activity. The preparation method is simple to operate, low in cost and easy to industrialize.

[0006] To achieve the above object, the present invention provides a method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen, comprising the following steps:

[0007] (1) Dissolve Ni(Ac)2·4H2O in 70 mL of methanol; slowly add ZIF-67 powder to the above solution and stir for 20 to 40 minutes. Perform hydrothermal reaction, filter, wash, and dry to obtain NiCo-LDH powder.

[0008] (2) Dissolve thioacetamide in ethanol; dissolve Cd(Ac)2·2H2O and Zn(Ac)2·2H2O in 30 mL of deionized water, then add the above-mentioned dissolved solution, stir for 5 to 15 minutes, add NiCo-LDH, stir for 10 to 30 minutes, and obtain a mixed solution. The mixed solution is subjected to a hydrothermal reaction, and the obtained powder is filtered, washed, and dried to obtain a ZnCdS2-NiCo photocatalyst.

[0009] Preferably, in the above technical solution, the amount of Ni(Ac)2·4H2O used in step (1) is 0.6 to 2.6 mmol.

[0010] Preferably, in the above technical solution, the amount of ZIF-67 used in step (1) is 20 to 160 mg.

[0011] Preferably, in the above technical solution, the temperature during the hydrothermal reaction in step (1) is 90 to 150° C., and the reaction time is 3 to 9 hours.

[0012] Preferably, in the above technical solution, the drying temperature in step (1) is 50 to 90° C., and the drying time is 8 to 12 hours.

[0013] Preferably, in the above technical scheme, the molar ratio of Cd(Ac)2·2H2O:Zn(Ac)2·2H2O:thioacetamide in step (2) is n(Cd(Ac)2·2H2O):n(Zn(Ac)2·2H2O):n(thioacetamide)=1:1:2~4.

[0014] Preferably, in the above technical solution, the amount of NiCo-LDH used in step (2) is 5 to 60 mg.

[0015] Preferably, in the above technical solution, the temperature of the hydrothermal reaction of the mixed solution in step (2) is 150-210° C., and the reaction time is 6-10 h.

[0016] Preferably, in the above technical solution, the drying temperature in step (2) is 50 to 90° C., and the drying time is 8 to 12 hours.

[0017] Beneficial Effects

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The ZnCdS2-NiCo photocatalyst prepared by the method of the present invention can effectively improve the separation efficiency and surface activity of photogenerated charges, and greatly improve its photocatalytic activity. Under visible light illumination, it degrades waste plastics and produces hydrogen at the same time, and its hydrogen production rate reaches 48.62mmol·g -1 ·h -1 , which has practical application significance in simultaneously degrading waste plastics and producing hydrogen.

[0020] (2) The method for preparing ZnCdS2-NiCo photocatalyst of the present invention is simple to operate, low in cost, and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a field emission scanning electron microscope image of the ZnCdS2-NiCo photocatalyst prepared according to the method of the present invention.

[0022] Figure 2 1 is the X-ray diffraction pattern of ZnCdS2 and ZnCdS2-NiCo photocatalysts prepared according to the method of the present invention.

[0023] Figure 3 This is the element ratio diagram of the ZnCdS2-NiCo photocatalyst prepared according to the method of the present invention.

[0024] Figure 4 Graph showing the hydrogen production rate of the photocatalyst under different NiCo-LDH addition conditions prepared according to the method of the present invention.

[0025] Figure 5 It is a liquid nuclear magnetic resonance spectrum of the photocatalytic degradation of waste plastics by ZnCdS2 and ZnCdS2-NiCo photocatalysts prepared according to the method of the present invention. DETAILED DESCRIPTION

[0026] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings, but it should be understood that the protection scope of the present invention is not limited by the specific implementation modes.

[0027] Example 1

[0028] A method for preparing ZnCdS2 comprises the following steps:

[0029] (1) Dissolve 1.6 mmol Ni(Ac)2·4H2O in 70 mL methanol; slowly add 100 mg ZIF-67 powder to the above solution and stir for 30 minutes. Hydrothermally react at 120°C for 6 hours, filter, wash, and dry at 60°C for 10 hours to obtain NiCo-LDH powder.

[0030] (2) 6.25mmol of thioacetamide was dissolved in ethanol; 2.5mmol of Cd(Ac)2·2H2O and 2.5mmol of Zn(Ac)2·2H2O were dissolved in 30mL of deionized water, and then the above-mentioned dissolved solution was added, stirred for 10 minutes, and then 0mg of NiCo-LDH was added and stirred for 20 minutes to obtain a mixed solution. The mixed solution was hydroheated at 170°C for 8h, and the obtained powder was filtered, washed, and dried at 60°C for 10h to obtain a ZnCdS2 photocatalyst. The X-ray diffraction pattern of the obtained ZnCdS2 was detected, as shown in FIG. Figure 2 shown.

[0031] Example 2

[0032] A method for preparing ZnCdS2-NiCo comprises the following steps:

[0033] (1) Dissolve 1.6 mmol Ni(Ac)2·4H2O in 70 mL methanol; slowly add 100 mg ZIF-67 powder to the above solution and stir for 30 minutes. Hydrothermally react at 120°C for 6 hours, filter, wash, and dry at 60°C for 10 hours to obtain NiCo-LDH powder.

[0034] (2) 6.25mmol of thioacetamide was dissolved in ethanol; 2.5mmol of Cd(Ac)2·2H2O and 2.5mmol of Zn(Ac)2·2H2O were dissolved in 30mL of deionized water, and then the above-mentioned dissolved solution was added, stirred for 10 minutes, and then 5mg of NiCo-LDH was added and stirred for 20 minutes to obtain a mixed solution. The mixed solution was hydroheated at 170°C for 8h, and the obtained powder was filtered, washed, and dried at 60°C for 10h to obtain a ZnCdS2-NiCo photocatalyst.

[0035] Example 3

[0036] A method for preparing ZnCdS2-NiCo comprises the following steps:

[0037] (1) Dissolve 1.6 mmol Ni(Ac)2·4H2O in 70 mL methanol; slowly add 100 mg ZIF-67 powder to the above solution and stir for 30 minutes. Hydrothermally react at 120°C for 6 hours, filter, wash, and dry at 60°C for 10 hours to obtain NiCo-LDH powder.

[0038] (2) 6.25mmol of thioacetamide was dissolved in ethanol; 2.5mmol of Cd(Ac)2·2H2O and 2.5mmol of Zn(Ac)2·2H2O were dissolved in 30mL of deionized water, and then the above-mentioned dissolved solution was added, and after stirring for 10 minutes, 15mg of NiCo-LDH was added and stirred for 20 minutes to obtain a mixed solution. The mixed solution was hydroheated at 170°C for 8h, and the obtained powder was filtered, washed, and dried at 60°C for 10h to obtain a ZnCdS2-NiCo photocatalyst. The field emission scanning electron microscopy image of the prepared ZnCdS2-NiCo was detected, as shown in FIG. Figure 1 As shown; the X-ray diffraction pattern of ZnCdS2-NiCo obtained by detection is as follows Figure 2 As shown; the element ratio diagram of ZnCdS2-NiCo obtained by detection, as shown Figure 3 shown.

[0039] Example 4

[0040] A method for preparing ZnCdS2-NiCo comprises the following steps:

[0041] (1) Dissolve 1.6 mmol Ni(Ac)2·4H2O in 70 mL methanol; slowly add 100 mg ZIF-67 powder to the above solution and stir for 30 minutes. Hydrothermally react at 120°C for 6 hours, filter, wash, and dry at 60°C for 10 hours to obtain NiCo-LDH powder.

[0042] (2) 6.25mmol of thioacetamide was dissolved in ethanol; 2.5mmol of Cd(Ac)2·2H2O and 2.5mmol of Zn(Ac)2·2H2O were dissolved in 30mL of deionized water, and then the above-mentioned dissolved solution was added, stirred for 10 minutes, and then 30mg of NiCo-LDH was added and stirred for 20 minutes to obtain a mixed solution. The mixed solution was hydroheated at 170°C for 8h, and the obtained powder was filtered, washed, and dried at 60°C for 10h to obtain a ZnCdS2-NiCo photocatalyst.

[0043] Example 5

[0044] A method for preparing ZnCdS2-NiCo comprises the following steps:

[0045] (1) Dissolve 1.6 mmol Ni(Ac)2·4H2O in 70 mL methanol; slowly add 100 mg ZIF-67 powder to the above solution and stir for 30 minutes. Hydrothermally react at 120°C for 6 hours, filter, wash, and dry at 60°C for 10 hours to obtain NiCo-LDH powder.

[0046] (2) 6.25mmol of thioacetamide was dissolved in ethanol; 2.5mmol of Cd(Ac)2·2H2O and 2.5mmol of Zn(Ac)2·2H2O were dissolved in 30mL of deionized water, and then the above-mentioned dissolved solution was added, stirred for 10 minutes, and then 60mg of NiCo-LDH was added and stirred for 20 minutes to obtain a mixed solution. The mixed solution was hydroheated at 170°C for 8h, and the obtained powder was filtered, washed, and dried at 60°C for 10h to obtain a ZnCdS2-NiCo photocatalyst.

[0047] Example 6

[0048] A method for preparing ZnCdS2-NiCo comprises the following steps:

[0049] (1) Dissolve 1.6 mmol Ni(Ac)2·4H2O in 70 mL methanol; slowly add 100 mg ZIF-67 powder to the above solution and stir for 20 minutes. Hydrothermally react at 90°C for 3 hours, filter, wash, and dry at 50°C for 10 hours to obtain NiCo-LDH powder.

[0050] (2) Dissolve 5 mmol of thioacetamide in ethanol; dissolve 2.5 mmol of Cd(Ac)2·2H2O and 2.5 mmol of Zn(Ac)2·2H2O in 30 mL of deionized water, then add the above-mentioned dissolved solution, stir for 5 minutes, add 10 mg of NiCo-LDH, stir for 20 minutes, and obtain a mixed solution. The mixed solution is hydroheated at 150°C for 6 hours, and the obtained powder is filtered, washed, and dried at 50°C for 8 hours to obtain a ZnCdS2-NiCo photocatalyst.

[0051] Example 7

[0052] A method for preparing ZnCdS2-NiCo comprises the following steps:

[0053] (1) Dissolve 1.6 mmol Ni(Ac)2·4H2O in 70 mL methanol; slowly add 100 mg ZIF-67 powder to the above solution and stir for 30 minutes. Hydrothermally react at 150°C for 9 hours, filter, wash, and dry at 90°C for 12 hours to obtain NiCo-LDH powder.

[0054] (2) 10 mmol of thioacetamide was dissolved in ethanol; 2.5 mmol of Cd(Ac)2·2H2O and 2.5 mmol of Zn(Ac)2·2H2O were dissolved in 30 mL of deionized water, and then the above-mentioned dissolved solution was added, stirred for 15 minutes, and then 60 mg of NiCo-LDH was added and stirred for 20 minutes to obtain a mixed solution. The mixed solution was hydroheated at 210°C for 8 hours, and the obtained powder was filtered, washed, and dried at 90°C for 12 hours to obtain a ZnCdS2-NiCo photocatalyst.

[0055] 20 g of polylactic acid powder was added to 400 mL of 10 M NaOH solution and stirred in a 40 °C oil bath for 24 h. The concentration of polylactic acid after pretreatment was 50 mg·L -1 . Photocatalytic degradation of waste plastics and hydrogen production were carried out in a sealed quartz reactor. The light source was a 300W xenon lamp (CEL-HXF300F3) equipped with a 400nm cutoff filter. 1.5mg of the photocatalyst powder prepared in the above embodiment was dispersed in 40mL of pretreated polylactic acid solution for reaction. Before photocatalytic degradation of waste plastics and hydrogen production, the reactor was purged with nitrogen (N2) for 30min to remove the air in the reactor. During the reaction, the solution was constantly stirred to maintain uniformity and was kept at room temperature by circulating cooling water. 1ml of gas was regularly extracted from the sealed quartz reactor every hour and measured by gas chromatography (GC7920-T). Each photocatalyst was tested three times under the same conditions and the average value was taken. Figure 4 The graphs show the hydrogen production rates of the photocatalysts prepared under different NiCo-LDH addition conditions in Examples 1-5. Figure 5 Shown are the liquid nuclear magnetic resonance spectra of the solution of the waste plastic pre-treated before irradiation and the liquid nuclear magnetic resonance spectra of the waste plastic solution after irradiation reaction for 24 hours in Example 1 and Example 3.

[0056] The foregoing descriptions of specific exemplary embodiments of the present invention are intended to be illustrative and exemplary. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is apparent that many changes and variations may be made in light of the foregoing teachings. The exemplary implementations are selected and described for the purpose of explaining the specific principles and practical applications of the present invention, thereby enabling those skilled in the art to implement and utilize the various exemplary embodiments of the present invention and the various selections and variations. The scope of the present invention is intended to be defined by the claims and their equivalents.

Claims

1. A method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen, characterized by comprising the following steps: (1) Dissolve Ni(Ac)2·4H2O in 70 mL of methanol; slowly add ZIF-67 powder to the above solution and stir for 20 to 40 minutes; perform hydrothermal reaction, filter, wash, and dry to obtain NiCo-LDH powder; (2) dissolving thioacetamide in ethanol; dissolving Cd(Ac)2·2H2O and Zn(Ac)2·2H2O in 30 mL of deionized water, then adding the above-mentioned dissolved solution, stirring for 5 to 15 minutes, adding NiCo-LDH, stirring for 10 to 30 minutes, and obtaining a mixed solution; subjecting the mixed solution to a hydrothermal reaction, filtering the obtained powder, washing it, and drying it to obtain a ZnCdS2-NiCo photocatalyst.

2. The method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen according to claim 1, characterized in that The amount of Ni(Ac)2·4H2O used in step (1) is 0.6 to 2.6 mmol.

3. The method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen according to claim 1, characterized in that The amount of ZIF-67 used in step (1) is 20 to 160 mg.

4. The method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen according to claim 1, characterized in that The temperature during the hydrothermal reaction in step (1) is 90 to 150° C., and the reaction time is 3 to 9 hours.

5. The method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen according to claim 1, characterized in that The drying temperature in step (1) is 50 to 90° C., and the drying time is 8 to 12 hours.

6. The method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen according to claim 1, characterized in that In step (2), the molar ratio of Cd(Ac)2·2H2O, Zn(Ac)2·2H2O and thioacetamide is n(Cd(Ac)2·2H2O):n(Zn(Ac)2·2H2O):n(thioacetamide)=1:1:2~4.

7. The method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen according to claim 1, characterized in that The amount of NiCo-LDH used in step (2) is 5 to 60 mg.

8. The method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen according to claim 1, characterized in that The temperature of the hydrothermal reaction of the mixed solution in step (2) is 150-210° C., and the reaction time is 6-10 hours.

9. The method for preparing a catalyst for photocatalytic degradation of waste plastics and production of hydrogen according to claim 1, characterized in that The drying temperature in step (2) is 50 to 90° C., and the drying time is 8 to 12 hours.